EDUCATION IN THE PATTERNS OF DIGITAL CULTURE: THE INDIVIDUALITY OF THE DETERMINISTIC SUBJECT - Kamardash, Nataliya (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
The article presents the problem of formation and determination of the individuality of the subject included in the world of digital culture. The study focuses on educational practices as one of the key factors influencing human subjectivity. The methodological basis of this research is a critical analysis and a multidisciplinary approach. This made it possible to consider a person, his characteristics and the problems of his personality in the postmodern era, as well as to determine the features of the current educational paradigm by comparing modern and postmodern educational models. The active development of mass media and Internet communications in the second half of the XX century is considered one of the factors that contributed to the significant ontological, axiological and anthropological transformations of modern culture, and also became one of the key factors in the formation of digital culture. The category of homo digitalis is explained as a unique phenomenon of the XXI century, its analysis is presented from different positions, including the definition of negative trends: decline of reflection, banalization of the New, primitive subjectivism, laziness, inability and unwillingness of analytical and critical mental activity, psychological problems, deviant manifestations, pedagogical vicissitudes and conflicts based on confrontations between generations, etc. Rejecting logocentrism and a rigid evaluative position, the study made an attempt to overcome skepticism regarding the expansion of digitalization into the educational process in the context of the modern problem of the massive introduction of distance education caused by the pandemic. It is proposed not to stigmatize the problems of individuality, which are characteristic of modern culture, as completely controlled by manipulative technologies, especially in relation to educational practices.